Analysis of Plot Structure in Desiree Baby’s Short Story by Kate Chopin - Suarnanda, Ni Kadek Dea Nirmala; Laksminy, Luh Putu; Sosiowati, I Gusti Ayu Gde (VISA: Journal of Vision and Ideas, 2024)
Desiree Baby is one of the American literature short stories written by Kate Chopin set in Louisiana during the late 19th century. The story explores themes of race, identity, and societal prejudice in the late 19th century. The story examines the destructive power of the complexities of racial identity in a social context through its engaging characters and storyline. This study aims to analyze the intrinsic elements especially the structure of the plot in a short story entitled “Desiree Baby” by Kate Chopin. The data was taken from the textual short story that contains the intrinsic elements. The data was collected by descriptive method with the form of research that is qualitative. Also, the data was obtained by reading, observing, collecting, and identifying the material that related to the theory. The data were analyzed using the theory contained in the book Mastering English Literature by Richard Gill (1995). The results showed that the short story "Desiree Baby" by Kate Chopin contains five crucial elements of the plot as stated by Gill (1995). The five elements of the plot consist of the situation, trajectory, proleptic events, and reversal & discovery.